The TRPM2 Ion Channel Regulates Inflammatory Functions of Neutrophils During Listeria monocytogenes Infection - Robledo-Avila, Frank H.; Ruiz-Rosado, Juan de Dios; Brockman, Kenneth L.; Partida-Sánchez, Santiago (Frontiers in Immunology, 2020)
During infection, phagocytic cells pursue homeostasis in the host via multiple mechanisms that control microbial invasion. Neutrophils respond to infection by exerting a variety of cellular processes, including chemotaxis, activation, phagocytosis, degranulation and the generation of reactive oxygen species (ROS). Calcium (Ca2+) signaling and the activation of specific Ca2+ channels are required for most antimicrobial effector functions of neutrophils. The transient receptor potential melastatin-2 (TRPM2) cation channel has been proposed to play important roles in modulating Ca2+ mobilization and oxidative stress in neutrophils. In the present study, we use a mouse model of Listeria monocytogenes infection to define the role of TRPM2 in the regulation of neutrophils’ functions during infection. We show that the susceptibility of Trpm2-/- mice to L. monocytogenes infection is characterized by increased migration rates of neutrophils and monocytes to the liver and spleen in the first 24h. Acute phase infection of L. monocytogenes in Trpm2-/- mice resulted in septic shock syndrome, characterized by increased serum levels of TNF-alpha, IL-6, and IL-10, but no decreased levels of IFN-gamma or IL-12. Furthermore, depletion of neutrophils demonstrated the critical role of these cells in regulating acute inflammation by conferring resistance of Trpm2-/- mice to L. monocytogenes infection. Gene expression and inflammatory cytokine analyses of infected tissues further confirmed the hyperinflammatory profile of Trpm2-/- neutrophils. Finally, the increased inflammatory properties of Trpm2-/- neutrophils correlated with the dysregulated cytoplasmic concentration of Ca2+ and potentiated membrane depolarization, in response to L. monocytogenes infection. In conclusion, our findings suggest that the TRPM2 channel plays critical functional roles in the regulation of the inflammatory properties of neutrophils during Listeria infection.